Proceedings of the Twenty-Seventh International Joint Conference on Artificial Intelligence 2018
DOI: 10.24963/ijcai.2018/18
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Auctions via Machine Learning-based Preference Elicitation

Abstract: Combinatorial auctions (CAs) are used to allocate multiple items among bidders with complex valuations. Since the value space grows exponentially in the number of items, it is impossible for bidders to report their full value function even in medium-sized settings. Prior work has shown that current designs often fail to elicit the most relevant values of the bidders, thus leading to inefficiencies. We address this problem by introducing a machine learning-based elicitation algorithm to identify which values to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 9 publications
0
36
0
Order By: Relevance
“…As part of their algorithm, they used kernelized support vector regressions (SVRs) to learn the nonlinear value functions of bidders. Recently, Brero, Lubin, and Seuken (2019) showed that their MLbased ICA achieves even higher efficiency than the CCA. However, because of runtime complexity issues, Brero, Lubin, and Seuken (2018; focused on SVRs with linear and quadratic kernels.…”
Section: Machine Learning and Mechanism Designmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of their algorithm, they used kernelized support vector regressions (SVRs) to learn the nonlinear value functions of bidders. Recently, Brero, Lubin, and Seuken (2019) showed that their MLbased ICA achieves even higher efficiency than the CCA. However, because of runtime complexity issues, Brero, Lubin, and Seuken (2018; focused on SVRs with linear and quadratic kernels.…”
Section: Machine Learning and Mechanism Designmentioning
confidence: 99%
“…Recently, Brero, Lubin, and Seuken (2019) showed that their MLbased ICA achieves even higher efficiency than the CCA. However, because of runtime complexity issues, Brero, Lubin, and Seuken (2018; focused on SVRs with linear and quadratic kernels. This leaves room for improvement, since bidders' valuations can have more complex structures than can be captured by linear or quadratic kernels.…”
Section: Machine Learning and Mechanism Designmentioning
confidence: 99%
See 1 more Smart Citation
“…One major difficulty arises from the fact that the true valuation functions v i are unknown to the auctioneer and can only be accessed through a limited amount of queries (typically less than 500 queries per bidder) called preference elicitation [48]. Machine learning based preference elicitation approaches overcome this issue by approximating the valuation functions by parametric functions, e.g., polynomials of degree two [48] or Gaussian processes [49]. The estimated parameters of these approximations are adaptively refined using a suitable querying strategy.…”
Section: Samplingmentioning
confidence: 99%
“…and have been a central topic in the study of Multi-Agent Systems. They have also experienced a recent interest in the AI community with works employing ML algorithms to overcome standard complexity problems (e.g., [5,6]).…”
Section: Introductionmentioning
confidence: 99%